Investigation of technologies of processing of big data - Balakayeva, G. T.; Darkenbayev, D. K.; Phillips, Chris (International Journal of Mathematics and Physics, 2017)
An overview of the technologies and methods is presented, on the basis of which the authors of this article model the processing of a large amount of data, developing a web application. In particular, it is proposed to combine models to improve the efficiency of processing large amounts of data. Large data set before traditional storage systems and processing a new challenge. This article analyzes possible methods their decisions, limitations that do not allow to do it effectively, and also provides an overview of three modern approaches to working with large data: NoSQL and real-time event flow processing. Analysis of large data requires the use of technology and the means to implement highly productive computing. The main factors of the problem are, first of all, the complexity and the second physical volume of the information collection. It should be noted that the actual processing of data includes the construction of the algorithm and the time for its description and debugging. Unique data collections require the development of unique algorithms, which increases the total processing time by an order of magnitude. <div id="SL_button" class="SL_ImTranslatorLogo" style="background: rgba(0, 0, 0, 0) url('moz-extension://a11bc875-1804-4fd7-8e5e-a70b44ba6b3c/content/img/util/imtranslator-s.png') repeat scroll 0% 0%; display: none; opacity: 1;"> G M T <input id="SL_locer" title="Зафиксировать язык" type="checkbox"> <select id="SL_lng_from" style="background: #ffffff url('moz-extension://a11bc875-1804-4fd7-8e5e-a70b44ba6b3c/content/img/util/select.png') no-repeat scroll 100% 0px;"><option value="en">Английский</option><option value="es">Испанский</option><option value="it">Итальянский</option><option value="kk">Казахский</option><option value="zh-TW">Китайский Трад</option><option value="zh-CN">Китайский Упр</option><option value="ko">Корейский</option><option value="ru">Русский</option><option value="tr">Турецкий</option><option value="fr">Французский</option></select> <select id="SL_lng_to" style="background: #ffffff url('moz-extension://a11bc875-1804-4fd7-8e5e-a70b44ba6b3c/content/img/util/select.png') no-repeat scroll 100% 0px;"><option value="en">Английский</option><option value="es">Испанский</option><option value="it">Итальянский</option><option value="kk">Казахский</option><option value="zh-TW">Китайский Трад</option><option value="zh-CN">Китайский Упр</option><option value="ko">Корейский</option><option selected="selected" value="ru">Русский</option><option value="tr">Турецкий</option><option value="fr">Французский</option></select> Звуковая функция ограничена 200 символами <input id="SL_BBL_locer" title="Показывать кнопку ImTranslator Bubble 3 секунд" checked="checked" type="checkbox"> Настройки : История : Обратная связь : Donate Закрыть